Motor imagery and engagement favour spatial reasoning. - Ianì, Francesco; Schaeken, Walter; Ras, Ivan Nabil; Bucciarelli, Monica (Memory & Cognition, 2023)
Based on the assumption that spatial reasoning relies on the construction of mental models of the states of affairs described in the premises, and on evidence that sensory-motor imagery can enhance cognitive abilities, we hypothesised that imagining moving the objects mentioned in the premises to the specific spatial locations should favour spatial reasoning. The results of Experiment 1 confirmed the prediction: when participants imagined moving the objects mentioned in the premises (dynamic-engagement condition), they drew accurate inferences faster compared with participants who merely read the premises (static-non-engagement condition). Experiment 2 was in part a replication of Experiment 1 but included two additional experimental conditions to control for possible effects of self-engagement in reasoning: in one condition, participants imagined that someone else was moving the objects (dynamic-non-engagement condition), and in the other condition, participants imagined that they were observing the objects (static-engagement condition). The results revealed an interaction between motor imagery and engagement in decreasing response times to spatial problems. We discuss the practical implications of the current results.